2018
DOI: 10.1038/s41467-018-05913-y
|View full text |Cite
|
Sign up to set email alerts
|

A plant Bro1 domain protein BRAF regulates multivesicular body biogenesis and membrane protein homeostasis

Abstract: Plant development, defense, and many physiological processes rely on the endosomal sorting complex required for transport (ESCRT) machinery to control the homeostasis of membrane proteins by selective vacuolar degradation. Although ESCRT core components are conserved among higher eukaryotes, the regulators that control the function of the ESCRT machinery remain elusive. We recently identified a plant-specific ESCRT component, FREE1, that is essential for multivesicular body/prevacuolar compartment (MVB/PVC) bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…Col-0, RabF2b-YFP (Wave2Y), Got1p homolog-YFP (Wave 22Y) seeds were obtained from the Arabidopsis Resource Center (ABRC) stock centre (Ohio, U.S.A.). Arabidopsis FLS2-GFP, pREM1.2::YFP:REM1.2, CLC-GFP, BRI1-GFP and BOR1-GFP marker lines were described previously (18, 57; 108, 109,110). Sterol mutants fkX224 , smt1-1 and their WT ecotypes were described previously (111, 112).…”
Section: Experimental Model and Subject Detailsmentioning
confidence: 99%
“…Col-0, RabF2b-YFP (Wave2Y), Got1p homolog-YFP (Wave 22Y) seeds were obtained from the Arabidopsis Resource Center (ABRC) stock centre (Ohio, U.S.A.). Arabidopsis FLS2-GFP, pREM1.2::YFP:REM1.2, CLC-GFP, BRI1-GFP and BOR1-GFP marker lines were described previously (18, 57; 108, 109,110). Sterol mutants fkX224 , smt1-1 and their WT ecotypes were described previously (111, 112).…”
Section: Experimental Model and Subject Detailsmentioning
confidence: 99%
“…Plantspecific substitutes for this subunit could be several ubiquitin receptors in the early endocytic pathway of plants (Mosesso et al, 2019). In Arabidopsis the conserved scaffolding protein, apoptosis-linked gene-2 interacting protein X (ALIX), binds membranes, ubiquitin, and K63-linked ubiquitin chains, and interacts with Vacuolar Sorting Protein 23A (VPS23A) and FYVE1 (Fab1, YOTB, Vac1, and EEA1)/FREE1 (FYVE DOMAIN PROTEIN REQUIRED FOR ENDOSOMAL SORTING 1), essential for ESCRT-I as well as ESCRT-III function (Cardona-Lopez et al, 2015;Kalinowska et al, 2015;Shen et al, 2018). The plantspecific FYVE1/FREE1 localizes to MVBs and binds ubiquitin as well as PtdIns(3)P, and furthermore interacts with the Src homology-3 (SH3) domain-containing protein 2 (SH3P2), VPS23A/B, and the ESCRT-III complex (Barberon et al, 2014;Gao et al, 2014;Kolb et al, 2015;Belda-Palazon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using state-of-the-art techniques revealed many details on the underlying mechanisms of plant membrane transport (reviewed in Paez . Although many conserved trafficking regulators have been found to be as important in plants as in other organisms, at the same time, plant-specific regulators have also been identified (Gao et al, 2014;Kolb et al, 2015;Nagel et al, 2017;Reyes et al, 2014;Shen et al, 2018), providing a glimpse into the intriguing adaptation and evolution of this pathway.…”
Section: Tom1-like Proteins Are Ub Adaptor Proteins Expanded In Plantsmentioning
confidence: 99%
“…In mammals, an additional Bro1 domain-containing protein, His domain phosphotyrosine phosphatase (HD-PTP, also known as PTPN23), has been reported to be involved in ESCRT-dependent intracellular trafficking events (Ali et al, 2013; Gahloth et al, 2016). Besides ALIX, four Bro1 domain-containing proteins can be found in the Arabidopsis genome (Shen et al, 2018). Although a second Bro1 domain-containing protein named BRO1-DOMAIN PROTEIN AS FYVE1/FREE1 SUPPRESSOR (BRAF) has been shown to be involved in plant endosomal protein degradation, there is no obvious homolog of HD-PTP in the Arabidopsis genome (Shen et al, 2018).…”
Section: Tom1-like Proteins Are Ub Adaptor Proteins Expanded In Plantsmentioning
confidence: 99%
See 1 more Smart Citation